Non-completion of upper secondary school among female and male young adults in an Arctic sociocultural context; the NAAHS study - Bania, Elisabeth Valmyr; Lydersen, Stian; Kvernmo, Siv (BMC Public Health, 2016)
Publisher's version, source: http://doi.org/10.1186/s12889-016-3644-2 . BACKGROUND: Education is closely associated with health. Non-completion of upper secondary school influences academic achievement, employment, income and personal well-being. The purpose of the study is to explore predictors of non-completion of upper secondary school among female and male young adults in relation to mental health and educational factors in a socio-cultural, Arctic context. METHODS: The Norwegian Arctic Adolescent Health Study (NAAHS) is a cross-sectional, school-based survey that was conducted in 2003-2005. Eighty-three percent of the population of 5,877 10th graders participated; 49.1%females, 450 reported indigenous Sami ethnicity, and 304 reported Laestadian affiliation. Data from NAAHS were merged with registry data from the National Education Database (NUDB) Norway for 3,987 adolescents who gave their consent for follow-up studies. RESULTS: Non-completion of upper secondary school was 36.9 % among females and 36.6 % among males. Among females, predictors for non-completion were related to mental health symptoms, and among males, to residency in the northernmost and remote areas and self-reported functional difficulties at school, home and in leisure activities due to mental health problems. There was marginal significance between ethnicity and non-completion of upper secondary school, measured at 41.3 % for Sami and 36.8 % for non-Sami, respectively. CONCLUSIONS: The gender differences found in this study emphasize the need for gender-specific interventions in preventing non-completion of upper secondary school. There is a need to recognize and treat extensive pro-social behaviour and social problems in young females. Young males from remote areas and those who in early adolescence struggle with functional impairment due to mental health problems need early interventions in lower secondary school. Enhancing parents' and teachers' ability to detect symptoms and problems as well as low-threshold health services ...